Penggunaan Solution Focused Career Counseling untuk Meningkatkan Kemampuan Pengambilan Keputusan Karier Siswa SMPN 50 Surabaya - Achmad Jailani Sholeh; Najlatun Naqiyah; Retno Tri Hariastuti (MODELING: Jurnal Program Studi PGMI, 2021)
This research aims to test the use of group counseling with Solution Focused Career strategy to improve career decision making of students of SMP Negeri 50 Surabaya. The research design used was an experiment involving as many as 8 students of SMP Negeri 50 Surabaya who were selected by porposive random sampling. The instrument used is CDDQ (Career Decisionmaking Dificult Quetionare).The results showed that solution focused career counseling is enhancement for improving the career decision making of learners. This study provides a clarification on the application of handling career decision making with Solution Focused Career Counseling. During the Covid-19 pandemic, research was carried out in two ways, namely online and offline research. The results of the study showed an increase from the lowest pre-test results of 32 and the highest post-test results of 78 with an average of 4.50.